2021
DOI: 10.1186/s12879-021-06407-x
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term follow-up results after implementing a new strategy for the diagnosis and management of periprosthetic joint infections

Abstract: Background Periprosthetic joint infections (PJIs) represent one of the most serious complications associated with joint replacement surgeries, a complication also of modern orthopedic surgery despite the efforts that occurred in this field. Frequently PJIs lead to prolonged morbidity, increased costs and mortality. Methods We are conducting a single-center observational cohort ongoing study in the Academic Emergency Hospital Sibiu, Romania, study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The diagnosis and management of PJIs require adapted protocols for the treatment of biofilm-related infections and new and rapid diagnostic methods to be able to improve the eradication rate. However, there is no 100% certainty that the infection was eradicated [16].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis and management of PJIs require adapted protocols for the treatment of biofilm-related infections and new and rapid diagnostic methods to be able to improve the eradication rate. However, there is no 100% certainty that the infection was eradicated [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that surgery can also induce immunosuppression. For example, phagocytic activity in specific cells (PMN, monocytes, and macrophages) is reduced during the postoperative period, which makes patients more susceptible to infection [172][173][174][175][176][177][178][179][180][181][182][183][184].…”
Section: Orthopedic Surgeries and Inflammatory Signaturesmentioning
confidence: 99%
“…Some authors have recommended against antibiotic discontinuation for many years now [ 53 ] and perform the second stage under antibiotic therapy that is maintained for a total of at least 12 weeks, regardless of the duration of the time interval with the spacer. This approach has consistently shown good outcomes [ 54 , 55 ]. Ascione et al [ 56 ] directly compared both strategies in a total of 196 patients with PJI treated with a two-stage protocol.…”
Section: Antibiotic Holiday Periodmentioning
confidence: 99%
“…Unless the wound was slow to heal or there was extensive bone destruction, Haddad et al [ 58 ] reported no increase in reinfection rates by reducing the interval to 3 weeks. Several other papers have also demonstrated that it is possible to achieve good results with short intervals of 2–4 weeks provided that there are favorable bone and soft tissue conditions and in the absence of drug resistant microorganisms [ 53 55 , 59 ]. Furthermore, a number of studies have even shown an increased re-infection risk associated with prolonged time interval between stages [ 60 64 ].…”
Section: Time To Reimplantationmentioning
confidence: 99%